Rus Basınında Türkiye'nin Enerji Politikaları (1994-2014) - Hagverdiyeva, Aynura (My University, 2018)
ÖZETRUS BASININDA TÜRKİYE’NİN ENERJİ POLİTİKALARI (1994-2014)Soğuk Savaş’ın son bulması tüm dünya düzenini alt üst etmiş, hem politik, hem de ekonomik alanda büyük değişimlere sebep olmuştur. Bu olaydan en çok etkilenen bölge ise 1991 yılına kadar büyük bir kısmı SSCB sınırları içinde yer alan Avrasya olmuştur. Bu dönemde ülkelerin Avrasya bölgesine yaklaşımı ve bu coğrafyaya yönelik politikaları, uluslararası ilişkilerde esas istikametlerden birini teşkil etmeye başlamıştır. Soğuk Savaş döneminde NATO üyesi olarak ABD’nin yanında yer alan Türkiye, 20. yüzyılın 90’lı yıllarından itibaren değişen öncelikleri doğrultusunda kendine farklı bir yol çizmeye başlamıştır. Dolayısıyla Türkiye’nin Avrasya bölgesine yaklaşımı değişmiş, özellikle de enerji politikaları çerçevesinde yeni boyut kazanan enerji güvenliğinin sağlanması açısından bu bölgenin Türkiye için önemi artmıştır. Bölgede gerçekleştirilen enerji projelerinin en aktif katılımcılarından birine dönüşmesi, Türkiye’nin Avrasya’ya verdiği önemin bir göstergesidir. 1990’lı yılların sonu 2000’li yılların başında bu projeler çerçevesinde enerji kaynaklarının Doğu’dan Batı’ya ulaştırılmasında transit ülke görevini üstlenen Türkiye, son 10 yılda bölgede enerji merkezi olma yolunda hızla ilerlemektedir. Bu bağlamda Türkiye’nin yürüttüğü enerji politikaları, hem ulusal hem de uluslararası basın tarafından merakla izlenmekte ve yankı uyandırmaktadır. Bu çalışmada İzvestiya ve Nezavisimaya Gazeta örneğinde Türkiye’nin enerji politikalarının Rus basınındaki yansımalarına odaklanılmıştır. Teun van Dijk’ın Eleştirel Söylem Analizi yöntemi kullanılarak yapılan bu çalışmayla Rusya’nin Nezavisimaya Gazeta ve İzvestiya gazetelerinin Türkiye’nin enerji politikaları ile ilgili haber yapımında tarafsız bir duruş sergileyemedikleri, konuya Rusya hükümetinde temsil olunanların bakış açısına paralel bir perspektiften baktıkları ve sonuç olarak da ideolojik devlet aygıtı işlevini yerine getirerek, egemen ideolojiyi yeniden ürettikleri ortaya konulmuştur.

ABSTRACTTURKEY’S ENERGY POLICIES ON RUSSIAN PRESS (1994-2014)The end of the Cold War has overturned the whole world order and has caused great changes in both political and economic arena. The region most affected by this event was Eurasia, which main part was in the territory of the USSR until 1991. In this period, countries approach to the Eurasian region and their policies towards this geography have begun to form one of the main directions in the international relations. During the Cold War as a member of NATO Turkey was standing by side of the United States and has begun to take different way according to its changing priorities since the 90s years of the 20th century. Therefore, the approach of Turkey to Eurasia has changed, especially in terms of ensuring energy security gained new dimension in the framework of energy politics has increased importance of this region for Turkey. Turning into one of the most active participants of the energy projects in the region is an indication of the importance given by Turkey to Eurasia. At the end of 1990s and at the beginning of 2000s within the framework of this project assuming the duty transit country in the transportation of energy resources from East to West, Turkey has been progressing rapidly in the way of becoming the energy hub in the region for the last 10 years. Whereas Turkey, the end of the 1990s, at the beginning of the 2000s had just assumed the duty transit country for the transportation of energy resources from the East to the West. In this context, Turkey’s energy policies are following with interest both by national and international press and it is creating reactions. In this thesis it was focused on the reflection of Turkey energy policies on the Russian press, the case of Izvestia and Nezavisimiya Gazeta. With the study using Teun van Dijk's Critical Discourse Analysis method Russia's Nezavisimaya Gazeta and Izvestia newspaper could not play a neutral stance in making news related to the energy policies of Turkey, it was revealed that they were looking from a perspective paralel to the point of view of the representatives of the Russian government and as a result they have regenerated the dominant ideology by fulfilling the function of an ideological state apparatus.
Keywords: at the beginning of the 2000s had just assumed the duty transit country for the transportation of energy resources from the East to the West; At the end of 1990s and at the beginning of 2000s within the framework of this project assuming the duty transit country in the transportation of energy resources from East to West; Basın; countries approach to the Eurasian region and their policies towards this geography have begun to form one of the main directions in the international relations; Doğal Gaz; During the Cold War as a member of NATO Turkey was standing by side of the United States and has begun to take different way according to its changing priorities since the 90s years of the 20th century; Energy policy; Enerji Politikaları; Enerji politikası; especially in terms of ensuring energy security gained new dimension in the framework of energy politics has increased importance of this region for Turkey; In this context; In this period; In this thesis it was focused on the reflection of Turkey energy policies on the Russian press; it was revealed that they were looking from a perspective paralel to the point of view of the representatives of the Russian government and as a result they have regenerated the dominant ideology by fulfilling the function of an ideological state apparatus; İzvestiya Gazetesi; Nezavisimiya Gazeta ABSTRACTTURKEY’S ENERGY POLICIES ON RUSSIAN PRESS (1994-2014)The end of the Cold War has overturned the whole world order and has caused great changes in both political and economic arena; Petrol; Press; Rus Basını; Russia; Rusya; the approach of Turkey to Eurasia has changed; the case of Izvestia and Nezavisimiya Gazeta; the end of the 1990s; The region most affected by this event was Eurasia; Therefore; Turkey; Turkey has been progressing rapidly in the way of becoming the energy hub in the region for the last 10 years; Turkey’s energy policies are following with interest both by national and international press and it is creating reactions; Turning into one of the most active participants of the energy projects in the region is an indication of the importance given by Turkey to Eurasia; Türkiye; Whereas Turkey; which main part was in the territory of the USSR until 1991; With the study using Teun van Dijk's Critical Discourse Analysis method Russia's Nezavisimaya Gazeta and Izvestia newspaper could not play a neutral stance in making news related to the energy policies of Turkey